Effects of habitat degradation and fragmentation on butterfly biodiversity in West Kotawaringin, Central Kalimantan, Indonesia - HARMONIS HARMONIS; OSHLIFIN RUCMANA SAUD (Society for Indonesian Biodiversity, 2017)
Harmonis, Saud OR. 2016. Effects of habitat degradation and fragmentation on butterfly biodiversity in West Kotawaringin, Central Kalimantan. Biodiversitasx 18: 500-506. The main purpose of this study was to examine the effects of degradation and fragmentation habitats to butterfly communities. To be specific, species diversity, taxonomy structure, main species in every study sites were observed to find out the effects and correlation of each parameters. Field study was carried out in 8 sites in Kotawaringin Barat, Central Kalimantan Province, Indonesia. The specimens were collected using aerial insect nets and baited traps in January-February 2016. From the result of the study, the total of 1085 individual in 130 species was successfully collected. Based on distribution analysis using Shannon-Wiener index, the diversity of butterfly was in the range of middle to high categories (Hâ€™ = 2.7-3.5). Of another parameter analysis, it showed that butterfly communities were affected by degradation habitat, while fragmentation habitat did not influence to the butterfly communities. Furthermore, the range of degradation level in the study sites did not correlate with the number of species and taxonomy structures, but the distribution of the special-group of main species showed in correlation. Lexias dirtea was only found in dense forests (site S-7), then Neptis hylas and Parantica agleoides appeared in shrub habitat (site S-5 and S-6). The finding indicated that green patches have valuable contribution to conserve the ecosystem as valuable germplasm for butterflies and also arthropods.